Penguatan Ketahanan Pangan Berbasis Lokal Mendorong Implementasi Asta Cita dan Berkarakter Pancasila di Desa Kedungudi Trawas Mojokerto - Hendri Prastiyono; Mi’rojul Huda; Silkania Swarizona; Bambang Sigit Widodo; Muhammad Ilyas Marzuqi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
Villages play a strategic role as the smallest administrative unit within the government structure and as the centers of community life, supporting the achievement of the Sustainable Development Goals (SDGs). However, conditions observed in many villages—particularly in Kedungudi Village, Trawas, and Mojokerto—indicate a shift in community values driven by climate change, urbanization, and the limited contributions of local government. Kedungudi Village possesses diverse resources that can be optimized, including local wisdom, social capital, and community solidarity. Therefore, there is a need to provide capacity building on locally based food security that is tolerant and respects diversity within the village community. In this context, a community service program (Pengabdian kepada Masyarakat/PKM) implemented in UNESA’s assisted “Pancasila pilot village” in Kedungudi has generated benefits through the dissemination of good practices. This program aims to strengthen locally based food security to reinforce the Asta Cita agenda and Pancasila character among residents of Kedungudi Village, Trawas Subdistrict, Mojokerto Regency. The participants comprised 21 community members: two village officials, five members of the youth organization (Karang Taruna), and 14 representatives of farmer and non-farmer groups. The program’s intended outcomes included a substantial improvement in locally based food security as an instrument for strengthening the Asta Cita agenda and the Pancasila character of Kedungudi residents. To achieve these outcomes, the program employed a direct capacity-building model delivered through two on-the-job training sessions. The training activities incorporated a door-to-door approach (DTD) and focus group discussions (FGDs). To ensure program sustainability, participants were organized into peer community groups, facilitated by peer educators from the PKM lecturer team. Each peer group is expected to further develop knowledge and disseminate it to other residents within the community.